DVGW이론에 따른 상수관망의 부식방지에 관한 연구 - 추태호(Tai-Ho Choo); 김하일(Ha-Il Kim); 옥치율(Chi-Youl Ok); 제성진(Sung-Jin Je) (한국콘텐츠학회 논문지, 6(11), 2006)
Leakage of waterworks pipe line net cause loss of water resources, additional foundation of pressurization facilities from pressure loss and soil weakening near leaked pipe line, etc.. This makes it difficult to maintain and manage waterworks pipe line net and so cause serious economic loss. The rate of accounted water can be improved by monitoring always water pressure and flux, and so on. from isolated region, preparing positively against leakage accident and preventing leakage from occurring. Actually after isolating region, average rate of accounted water in this region went up 88.94% by continuously monitoring control of water pressure and inflow rate. It is about 9.44% higher than that of Busan metropolitan city in 2003, 79.5%. 상수도관망에서 발생하는 누수현상은 수자원의 손실뿐만 아니라 압력손실로 인한 추가적 가압 설비의 필요성 및 누수 되는 관로 주변의 토질의 약화 등을 초래하여 관망의 유지관리를 어렵게 하고, 심각한 경제적 손실을 야기하고 있다. 본 연구는 구역고립으로 인한 수압과 유량 등을 상시 모니터링 하여 누수사고의 적극적인 대처와 누수발생을 미연에 방지함으로써 유수율을 향상시킬 수 있다. 실제 구역고립 후 계속되는 수압조절 및 유입유량의 모니터링에 인하여 구역 내 유수율 산정결과 평균 유수율은 88.94%로서 부산광역시 2003년도의 유수율 79.5%보다 9.44% 높게 조사되었다.